Coexisting conditions and concomitant medications do not affect venetoclax management and survival in chronic lymphocytic leukemia. (October 2022) - Frustaci, Anna Maria; Del Poeta, Giovanni; Visentin, Andrea; Sportoletti, Paolo; Fresa, Alberto; Vitale, Candida; Murru, Roberta; Chiarenza, Annalisa; Sanna, Alessandro; Mauro, Francesca Romana; Reda, Gianluigi; Gentile, Massimo; et al.
Background: The question of which parameters may be informative on venetoclax outcome in chronic lymphocytic leukemia (CLL) is still unclear. Furthermore, the choice to treat with venetoclax can be challenging in patients with baseline characteristics or comorbidities that may potentially favor some specific adverse events. Objectives: This study was aimed to evaluate whether age, fitness status, patients'/disease characteristics, or concomitant medications may predict outcomes in CLL patients receiving venetoclax. Design: Retrospective observational study. Methods: Impact of age, presence of Cumulative Illness Rating Scale (CIRS) >6 or severe organ impairment (CIRS3+), Eastern Cooperative Oncology Group–Performance Status (ECOG-PS), renal function, and concomitant medications were retrospectively analyzed on treatment management (definitive discontinuation due to toxicity, discontinuation due to toxicity, Tox-DTD; permanent dose reduction, PDR) and survival [progression free survival (PFS), event free survival (EFS), overall survival (OS)] in unselected patients receiving venetoclax monotherapy in common practice. Results: A total of 221 relapsed/refractory patients were included. Tox-DTD and PDR were reported in 5.9% and 21.7%, respectively, and were not influenced by any fitness parameter, age, number or type of concomitant medication, baseline neutropenia, or impaired renal function. None of these factors were associated with tumor lysis syndrome (TLS) development. Age and coexisting conditions had no influence on PFS and EFS. At univariate analysis, OS was significantly shorter only in patients with ECOG-PS >1 ( p  < 0.0001) and elderly (⩾65 years) with CIRS >6 ( p  = 0.014) or CIRS3+ ( p  = 0.031). ECOG-PS >1 retained an independent role only for EFS and OS. While Tox-DTD affected all survival outcomes, no differences in PFS were reported among patients permanently reducing dose or interrupting venetoclax for > 7 days. Conclusion: Clinical outcome with venetoclax is not influenced by comorbidities, patients' clinical characteristics, or concomitant medications. Differently from other targeted therapies, this demonstrates that, except ECOG-PS, none of the parameters generally considered for treatment choice, including baseline neutropenia or impaired renal function, should rule the decision process with this agent. Anyway, if clinically needed, a correct drug management does not compromise treatment efficacy and may avoid toxicity-driven discontinuations. Plain Language Summary: Chapter 1: Why was this study done? Chapter 2: Which are the main findings of the study? Chapter 3: How these findings may impact on clinical practice? Coexisting conditions and concomitant medications do not affect venetoclax management and survival in chronic lymphocytic leukemia  The question of which parameters may be informative on venetoclax outcome in chronic lymphocytic leukemia is still unclear. Furthermore, the choice to treat with venetoclax can be challenging in patients with baseline characteristics or comorbidities that may potentially favor some specific adverse events (e.g. compromised renal function or baseline neutropenia).  In our large series of patients treated outside of clinical trials, we demonstrated that neither age, fitness, comorbidities nor concomitant medications impact on venetoclax management and survival. Importantly, patients presenting with baseline neutropenia or impaired renal function did not have a higher rate of dose reductions or toxicity-driven discontinuations, thus further underlining that venetoclax may be safely administered even in those categories with no preclusions.  Differently from other targeted agents, our data demonstrate that none of the baseline factors commonly considered in treatment decision process retains a role with venetoclax. Finally, permanent dose reductions and temporary interruptions did not adversely impact PFS suggesting that, if clinically needed, a correct drug management should be adopted with no risk of compromising venetoclax efficacy.